The English and Welsh perspective on legal aid for crime victims - Taylor, Louise (My University, 2014)
The purpose of this paper is to give a brief overview of the English and Welsh Criminal Justice System and to explain the role of crime victims within it; to offer an insight into some of the soft law provisions that have been developed in England and Wales as alternatives to more formal provisions such as legal aid in offering protection and support to crime victims; and to question whether a right to legal aid to provide independent legal representation (ILR) for victims should and could be developed in this jurisdiction.
Keywords: The English and Welsh perspective on legal aid